2012
DOI: 10.3389/fphar.2012.00146
|View full text |Cite
|
Sign up to set email alerts
|

Beta Amyloid Differently Modulate Nicotinic and Muscarinic Receptor Subtypes which Stimulate in vitro and in vivo the Release of Glycine in the Rat Hippocampus

Abstract: Using both in vitro (hippocampal synaptosomes in superfusion) and in vivo (microdialysis) approaches we investigated whether and to what extent β amyloid peptide 1–40 (Aβ 1–40) interferes with the cholinergic modulation of the release of glycine (GLY) in the rat hippocampus. The nicotine-evoked overflow of endogenous GLY in hippocampal synaptosomes in superfusion was significantly inhibited by Aβ 1–40 (10 nM) while increasing the concentration to 100 nM the inhibitory effect did not further increase. Both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 54 publications
(65 reference statements)
0
15
0
Order By: Relevance
“…Thus, unlike nano-molar concentrations of A␤, pM concentrations of the peptide did not require APP to produce their synaptic effects. We then turned on ␣7nAChRs because of their interplay with A␤ in physiological conditions (Puzzo et al, 2008(Puzzo et al, , 2011Zappettini et al, 2012;Lawrence et al, 2014). When slices from ␣7nAChRs KO (␣7-KO) mice were treated with 200 pM oA␤ 42 , the decrease of PPF and the conversion of E-LTP to L-LTP were not elicited (Fig.…”
Section: Effect Of Picomolar Concentrations Of Oa␤ 42 On Short-term Amentioning
confidence: 99%
“…Thus, unlike nano-molar concentrations of A␤, pM concentrations of the peptide did not require APP to produce their synaptic effects. We then turned on ␣7nAChRs because of their interplay with A␤ in physiological conditions (Puzzo et al, 2008(Puzzo et al, , 2011Zappettini et al, 2012;Lawrence et al, 2014). When slices from ␣7nAChRs KO (␣7-KO) mice were treated with 200 pM oA␤ 42 , the decrease of PPF and the conversion of E-LTP to L-LTP were not elicited (Fig.…”
Section: Effect Of Picomolar Concentrations Of Oa␤ 42 On Short-term Amentioning
confidence: 99%
“…Indeed, it has been reported that Aβ binds with high affinity (in the picomolar range) to α7 nAChRs in cortical regions and in the hippocampus in AD, and with about 5,000 times lower affinity to α4β2 nAChRs [13], [14]. However, as a general mechanism, blockade of nAChRs by Aβ may also affect, at concentrations similar to those used in the present study, the cholinergic control of neurotransmitter release, including glycine, glutamate, aspartate and GABA [47], [48].…”
Section: Discussionmentioning
confidence: 53%
“…In addition, it has been shown that Aβ oligimers are able to modulate the release of several neurotransmitters (dopamine, γ-aminobutyric acid, aspartate, glutamate) elicited by the stimulation of cholinergic muscarinic and nicotinic receptor (mAChR, nAChR) in different brain areas. Recently it was shown the activation of both α7 and α4β2 (nAChRs) as well as by the activation of mAChR modulate the Glycine release from hippocampal synaptosomes [101].…”
Section: Aβ 42 Oligomers Modulate Intracellular Ca2+ Transients Evokementioning
confidence: 99%